2018
DOI: 10.1371/journal.pone.0206388
|View full text |Cite
|
Sign up to set email alerts
|

Salinity stress accelerates nutrients, dietary fiber, minerals, phytochemicals and antioxidant activity in Amaranthus tricolor leaves

Abstract: Impact of salinity stress were investigated in three selected Amaranthus tricolor accessions in terms of nutrients, dietary fiber, minerals, antioxidant phytochemicals and total antioxidant activity in leaves. Salinity stress enhanced biochemical contents and antioxidant activity in A. tricolor leaves. Protein, ash, energy, dietary fiber, minerals (Ca, Mg, Fe, Mn, Cu, Zn, and Na), β-carotene, ascorbic acid, total polyphenol content (TPC), total flavonoid content (TFC), total antioxidant capacity (TAC) (DPPH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 41 publications
7
84
0
1
Order By: Relevance
“…Shukla et al 34 also reported positive associations in their earlier work in A. tricolor. Similarly, betacyanin, betaxanthin, and betalain showed positive and significant interrelationship among each of them and with TAC (ABTS + ), chlorophylls, TFC, TAC (DPPH), and TPC which was corroborated with the results of our earlier studies in amaranth 8,9,[20][21][22][23][24] indicating increase in any pigment was directly related to increment of another pigment. The positive and significant interrelationship of TAC (DPPH), pigments, TFC, TPC, and TAC (ABTS + ) indicated that pigments, TFC, and TPC exhibited strong antioxidant potential.…”
Section: Genotypessupporting
confidence: 89%
See 1 more Smart Citation
“…Shukla et al 34 also reported positive associations in their earlier work in A. tricolor. Similarly, betacyanin, betaxanthin, and betalain showed positive and significant interrelationship among each of them and with TAC (ABTS + ), chlorophylls, TFC, TAC (DPPH), and TPC which was corroborated with the results of our earlier studies in amaranth 8,9,[20][21][22][23][24] indicating increase in any pigment was directly related to increment of another pigment. The positive and significant interrelationship of TAC (DPPH), pigments, TFC, TPC, and TAC (ABTS + ) indicated that pigments, TFC, and TPC exhibited strong antioxidant potential.…”
Section: Genotypessupporting
confidence: 89%
“…The positive and significant interrelationship of TAC (DPPH), pigments, TFC, TPC, and TAC (ABTS + ) indicated that pigments, TFC, and TPC exhibited strong antioxidant potential. The significant negative association was observed between pigments vs. total carotenoids and pigments vs. beta-carotene, while total carotenoids and beta-carotene exhibited a significant positive association with TAC (ABTS + ), TAC (DPPH), TPC, and TFC which was corroborated with the results of our earlier studies in amaranth [20][21][22][23][24] . It indicated that the increment of any leaf pigment had a direct decrement of total carotenoids and beta-carotene.…”
Section: Genotypessupporting
confidence: 89%
“…The positive and significant interrelationships of TAC (DPPH), all phytopigments, TAC (ABTS + ), TFC, and TPC indicated that phytopigments, TFC, and TPC exhibited strong antioxidant potential. The significant negative association was observed between phytopigments vs. total carotenoids and phytopigments vs. beta-carotene, while total carotenoids and beta-carotene exhibited a significant positive association with TAC (ABTS + ), TAC (DPPH), TPC, and TFC which was corroborated with the results of our earlier studies in amaranth [20][21][22][23][24] . It indicated that the increment of any phytopigment had a direct decrement of total carotenoids and beta-carotene.…”
supporting
confidence: 89%
“…In Nokia the period of watering, as well as photosynthesis active radiation, had no the significant influence. In the study by Sarker et al [30] abiotic stress (salinity) in Amaranthus tricolor leaves observed a higher amount of total phenolic content in comparison to control variant without stress. Total phenolic acid content in tested samples of KWS Olof ranged from 0.60 to 0.84 mg CAE per g and in Nokia from 0.75 to 1.65 mg CAE per g. While in KWS Olof significant differences were not observed, in Nokia, radiation PAR = 400 µmol m −2 s −1 caused an increase of total phenolic acid content in comparison to PAR = 800 µmol m −2 s −1 in control and drought cultivation conditions.…”
Section: Antioxidant Activitymentioning
confidence: 93%